Systematic Review Of Physical, Psychosocial And Spiritual Impact Of Post Acute Stroke Patients With Home Dwelling Care Approach - Muqarrobin, Aoladul; Chayati, Nur (Jurnal Keperawatan Muhammadiyah, 2021)
Objective: Stroke is a severe problem that is physically, psychologically, and spiritually complex. There should be a consideration of increasing self-ability in stroke patients through continued care at home to help patients to improve their quality of life. This study aims to analyze the impact of home-based care on the physical, psychological, and spiritual conditions of post acute stroke patientsMethods: This research is a systematic review. The research source came from two databases, namely ProQuest and EBSCO, with the keywords "Stroke" AND "Home service" AND Physical "OR" Psychological "OR" Spiritual. " From the ProQuest database, there were 66,665 journals found, and from EBSCO, there were 69,501 journals. Out of all the articles, only 8 articles met the inclusion criteria. The article must relate to the types of rehabilitation of stroke patients at home with the outcomes seen in the physical, psychological, and spiritual patients. Articles must use quasi-experimental, pre-experimental, and RCT designs, were published in the last five years, namely from 2014 to 2019, and not in the form of protocols and the English language and full textResults: Â This research is a systematic review. The research source came from two databases, namely ProQuest and EBSCO, with the keywords "Stroke" AND "Home service" AND Physical "OR" Psychological "OR" Spiritual. " From the ProQuest database, there were 66,665 journals found, and from EBSCO, there were 69,501 journals. Out of all the articles, only 8 articles met the inclusion criteria. The article must relate to the types of rehabilitation of stroke patients at home with the outcomes seen in the physical, psychological, and spiritual patients. Articles must use quasi-experimental, pre-experimental, and RCT designs, were published in the last five years, namely from 2014 to 2019, and not in the form of protocols and the English language and full text.Conclusion: Home based care could improve the physical and psychological of stroke patient, however it also has spirituality impact with less evidenceÂ Â